2017
DOI: 10.4269/ajtmh.17-0290
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine–Primaquine versus Chloroquine Alone to Treat Vivax Malaria in Afghanistan: An Open Randomized Superiority Trial

Abstract: Abstract.Afghanistan’s national guidelines recommend primaquine (PQ) for radical treatment of Plasmodium vivax malaria, but this is rarely implemented because of concerns over potential hemolysis in patients who have G6PD deficiency. Between August 2009 and February 2014, we conducted an open-label, randomized controlled trial of chloroquine (CQ) alone versus chloroquine plus primaquine (0.25 mg base/kg/day for 14 days) (CQ+PQ) in patients aged 6 months and older with microscopy confirmed P. vivax infection. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…Providing radical cure with PQ reduced recurrences by a factor of 6, from 28.2% to 4.1%. Similar results have been reported in recent years from other sites in this region, from Afghanistan [25], Kolkata, West Bengal, India [26, 27], southwestern India [28, 29], northeastern Myanmar [30], and the Thailand–Myanmar border [23].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Providing radical cure with PQ reduced recurrences by a factor of 6, from 28.2% to 4.1%. Similar results have been reported in recent years from other sites in this region, from Afghanistan [25], Kolkata, West Bengal, India [26, 27], southwestern India [28, 29], northeastern Myanmar [30], and the Thailand–Myanmar border [23].…”
Section: Discussionsupporting
confidence: 89%
“…This emphasizes the necessity of follow-up for 1 year when assessing vivax malaria in areas with long-latency strains. In recent years, this has been shown in Afghanistan [25], Pakistan [33], and Mexico [34], where such strains are prevalent. In this study, at least one-fifth of the relapses would have been missed if follow-up stopped at 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 764 Pashtun patients presenting with acute vivax malaria (304 males, 460 females) and 699 Pashtun controls (342 males, 357 females) were studied; 236 healthy males came from the epidemiology study reported previously ( Awab et al, 2017 ) and the remaining control subjects came from the same locations as the clinical malaria studies ( Table 1 ; Figure 1 ). In the controls, the allele frequency of G6PD Med was estimated to be 7.8% (95% credible interval [CI], 6.3–9.5) under the assumption of Hardy–Weinberg equilibrium.…”
Section: Resultsmentioning
confidence: 99%
“…Primaquine has been reported to improve the treatment of chloroquine-resistant plasmodia with chloroquine (50,51).…”
Section: Primaquinementioning
confidence: 99%